Spontaneous Epithelioid Hemangiosarcoma in a Rhesus Monkey (Macaca mulatta) - Tsuchiya, Takayuki (American Association for Laboratory Animal Science, 2014)
Epithelioid hemangiosarcoma is a rare malignant endothelial neoplasia with a unique, predominantly epithelioid morphology. A 4-y-old rhesus monkey from our laboratory had multiple neoplastic nodules in a digit, limb skin, hindlimb muscle, and visceral organs including lung, heart, and brain. The nodules were composed of pleomorphic, polygonal, epithelioid, neoplastic cells that were arranged in sheets, nests, and cords and supported by variably dense fibrovascular connective tissue. The morphologic features of this tumor were predominantly epithelioid. However, some regions contained cystic spaces, clefts, and channel-like structures, all of which were lined with morphologically distinct neoplastic endothelial cells. These neoplastic cells, with or without epithelioid morphology, were positive immunohistochemically for CD31, factor VIII-related antigen, and vimentin. The presence of multiple metastatic nodules, high mitotic rate, and extensive Ki67-positive staining were consistent with malignancy. This report is the first description of epithelioid hemangiosarcoma in a rhesus monkey.